Translational Control in Liver Disease - Balvey, Alexandra; Fernandez, Mercedes (Frontiers in Physiology, 2021)
Chronic liver disease is one of the biggest threats to public health worldwide. Worryingly, the incidence of liver disease is dramatically rising due to the ageing of the population and the global epidemics of obesity. Both are major risk factors for chronic liver disease and adverse prognostic factors, causing an increase in mortality rate. It is of great concern that 80-95% of obese people have non-alcoholic fatty liver disease, the major precursor for liver failure and a global health challenge. Currently, the only curative treatment for advanced chronic liver disease is liver transplantation, which is, however, hampered by high treatment costs and the scarcity of donor organs. New strategies are therefore urgently needed to prevent and reverse chronic liver disease. And for that it is essential to understand better the molecular mechanisms underlying human disease. This review focuses on the abnormalities in the regulation of translation by RNA-binding proteins during chronic liver disease and their pathological impact on portal hypertension, fibrosis, steatosis, neovascularization and cancer development.